Perceived Aesthetics Visual Design Elements Of A Packaging Design: A Preliminary Study - Raja Abdul Rahman, Raja Intan Suhaylah; Bidin, Azman; Lim, Yan Peng (2016)

(untitled)
In this paper, an introduction to review of literatures on aesthetics that concern on the visual design elements. Several aspects are discussed: the visual design elements and the aesthetics values through product aesthetic evaluation. In a theoretical approach, qualitative method has been applied at this preliminary stage. Prior to previous studies, this paper implements the method of reviewing content analysis, interviews and actual survey and observations, whereas stimuli are in the consideration for future analysis. A set of survey items have been identified for evaluation purposes for future recordings. Referring to previous studies, it has evidently presented that packaging attributes and aesthetic design elements have a great influence towards the consumers. Identification of the visual design elements are incorporating best to ensemble the cultural values such as graphics and sizes, the shape, colors, illustration, logo and brand name, typography, pattern, decorations and other product facts. An evaluation towards aesthetic upon those elements resulting as a symbolic value inclusive of the packaging features such as shape and materials which have been found out to be informative (Becker, van Rompay, Schifferstein, & Galetzka, 2011). However, understanding between the theory and aesthetic judgment may progress to new findings in which are applicable in designing a packaging design prototype and would be seen as new design directions for SMEs food packaging in particularly in Malaysia. According to Desmet & Hekkert (2007), being an integrated discipline that requires aesthetic, marketing, ergonomic and engineering skills, which occur within type of multidisciplinary; it projects design research as a special subject. New concepts have been introduced in addition to adopting new concepts from other disciplines of design research in which may stimulate new design directions